PENDAMPINGAN UMKM KUE RUMAHAN: IMPELEMENTASI DIGITAL MARKETING DAN MANAJEMEN ANGGARAN - Ritali Evi Mudrikah; Ahmat Yahya; Ainun Putri Samsi; Desi Purnama Sari; Winda Juliandari (Jurnal Abdimas Multidisiplin, 2026)
Purpose: The purpose of this community service program is to strengthen the capacity of home-based cake MSMEs in Sukarame, Bandar Lampung, through intensive assistance focusing on the implementation of digital marketing strategies and the application of effective and structured budget management systems. This initiative aims to enhance the digital readiness of business owners, improve their ability to promote products online, and develop fundamental financial management skills to support business sustainability. Methodology/Approach: The study employed a participatory empowerment approach through four main stages: initial observation and needs assessment, training in digital marketing, training in business financial management, and monitoring-evaluation. The activities were conducted through direct workshops, hands-on practice, simulation of digital content creation, and guided preparation of simple financial reports using accessible tools such as Google Spreadsheet. Results/Findings: The program successfully improved the digital literacy of MSME actors, as evident from their ability to create and optimize business social media accounts, produce engaging promotional content, and understand the use of digital advertising features. Additionally, the participants demonstrated enhanced awareness and skills related to business budgeting, cash flow recording, and the separation of personal and business finances. The evaluation indicated a noticeable increase in the quality of promotional materials, customer engagement, and the consistency of financial recording practices. Limitations: The primary limitation of this activity lies in the short duration of implementation, which constrains long-term monitoring of participants’ progress. Furthermore, the limited availability of digital devices among some participants affected the depth of content creation training, requiring facilitators to adjust the intensity of practical sessions. Contribution: This program contributes to strengthening the digital economy ecosystem at the community level by empowering small business owners with practical knowledge that enhances competitiveness, market penetration, and financial management skills. It also adds to the growing body of community service literature related to the digitalization of MSMEs in Indonesia.Keywords: Digital Marketing, UMKM, Budget Management, Community Empowerment, Financial Literacy.